2021
DOI: 10.1057/s41599-020-00699-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis System for Emotional Behavior in Football (ASEB-F): matches of FC Red Bull Salzburg without supporters during the COVID-19 pandemic

Abstract: During the COVID-19 pandemic the “Austrian Bundesliga”—as in many other European football leagues—resumed the season around the end of May 2020 without supporters in the stadiums. These so-called “ghost games” represent a unique and unprecedented opportunity to study the effects of the (missing) audience on the behavior and experience of sports professionals. The present study is the first of its kind, aimed at addressing the psychological effects of these “ghost games” on football players, staff, and official… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
(8 reference statements)
2
12
1
Order By: Relevance
“…Our findings on significantly decreased yellow cards awarded for unfair sportsmanship are in line with results from recent research, where it was found that ghost games have an overall calming effect on players, staff and officials, with an increase in fair-play behavior (Leitner and Richlan, 2021 ). Regarding the significant increase in yellow cards awarded for criticism, we argue that this represents another effect which was also found in the same study: referees tend to engage themselves significantly less during protest or words fight behavior with players.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings on significantly decreased yellow cards awarded for unfair sportsmanship are in line with results from recent research, where it was found that ghost games have an overall calming effect on players, staff and officials, with an increase in fair-play behavior (Leitner and Richlan, 2021 ). Regarding the significant increase in yellow cards awarded for criticism, we argue that this represents another effect which was also found in the same study: referees tend to engage themselves significantly less during protest or words fight behavior with players.…”
Section: Discussionsupporting
confidence: 92%
“…This effect could result in increased (dysfunctional) aggressive behavior, which, in turn, results in more fierce tackles, fouls and ultimately in more bookings for fouls. This hypothesis, however, is contradictory to results from a recent study, which shows that about 20% fewer emotional situations can be observed between players, coaches, and referees due to the lack of an audience (Leitner and Richlan, 2021 ). Similarly, we cannot rule out the possibility that other factors have changed during ghost games that have contributed to a flattening of the home advantage.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In addition to economic issues, such as the viability of clubs without spectator revenues, the changed stadium atmosphere is particularly striking. Already at the beginning of the pandemic, there was anecdotal evidence that the behavior of players changed, e.g., toward referees, and recent studies indicate that the missing crowd indeed has an impact on the (nonverbal) behavior of players, staff and referees (Leitner & Richlan, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Besides qualitative interviews and self-report questionnaires, a promising approach was recently put forward by Leitner & Richlan (2021b). Their "Analysis System for Emotional Behavior in Football" (ASEB-F) is a video-based categorical analysis system of nonverbal behavior during football matches.…”
Section: Implications For Football Clubs and Organizers The Question Now Arises As To Whatmentioning
confidence: 99%